A role for macrophages in hematopoiesis in the embryonic head - Li, Zhuan (Blood, 2019)
Along with the aorta-gonad-mesonephros region, the head is a site of hematopoietic stem and progenitor cell (HS/PC) development in the mouse embryo. Macrophages are present in both these embryonic hemogenic sites, and recent studies indicate a functional interaction of macrophages with hematopoietic cells as they are generated in the aorta. Whereas brain macrophages or “microglia” are known to affect neuronal patterning and vascular circuitry in the embryonic brain, it is unknown whether macrophages play a role in head hematopoiesis. Here, we characterize head macrophages and examine whether they affect the HS/PC output of the hindbrain-branchial arch (HBA) region of the mouse embryo. We show that HBA macrophages are CD45(+)F4/80(+)CD11b(+)Gr1(−) and express the macrophage-specific Csf1r-GFP reporter. In the HBA of chemokine receptor-deficient (Cx3cr1(−/−)) embryos, a reduction in erythropoiesis is concomitant with a decrease in HBA macrophage percentages. In cocultures, we show that head macrophages boost hematopoietic progenitor cell numbers from HBA endothelial cells > twofold, and that the proinflammatory factor tumor necrosis factor-α is produced by head macrophages and influences HBA hematopoiesis in vitro. Taken together, head macrophages play a positive role in HBA erythropoiesis and HS/PC expansion and/or maturation, acting as microenvironmental cellular regulators in hematopoietic development.